Human Urban Arboviruses Can Infect Wild Animals and Jump to Sylvatic Maintenance Cycles in South America - Figueiredo, Luiz Tadeu Moraes (Frontiers in Cellular and Infection Microbiology, 2019)
The present study shows that the most prominent human arboviruses worldwide (dengue viruses 1, 2, 3, and 4, Chikungunya virus, and Zika virus) can infect wild animals and jump from urban to sylvatic maintenance cycles in South America, as did the yellow fever virus in the past. All these viruses are transmitted by the anthropophilic mosquito Aedes aegypti and cause epidemics throughout Brazil. The yellow fever virus is the oldest example of an urban arbovirus that became sylvatic in South America. Currently, the disease is a zoonosis of non-human primates that moves like a wave through forests of the Brazilian countryside, traveling thousands of kilometers, killing many animals and eventually infecting man. However, since 2016, this zoonotic wave has reached the highly populated areas of Southeast Brazil, producing the largest human outbreak in the past 60 years. As with the yellow fever virus, sylvatic cycles may occur with dengue, Chikungunya, and Zika. In order to become sylvatic, arboviruses require an apparently unlikely conjunction of factors to surprisingly take place. These arboviruses could start to infect sylvatic primates and be transmitted by Haemagogus mosquitoes that inhabit tree canopies. We mention here publications reporting evidence of sylvatic cycles of dengue, Chikungunya, and Zika virus in South America. Indeed, it is almost unfeasible to control these cycles of arboviruses since it is impossible to know where, when or why an arboviral spill-over would occur in wild animals. The sylvatic maintenance cycle could preclude the eradication of an arbovirus. Moreover, an arbovirus in a sylvatic cycle could re-emerge anytime, infecting humans and producing outbreaks. In case of the reemergence of an arbovirus, it is crucial to prevent the occurrence of an urban cycle as a spill-back from the sylvatic cycle.